Molecular mechanisms and enhanced functions of Hibiscus sabdariffa L—nanoliposomes as an emerging therapeutic strategy in UV and galactosamine skin aging-induced model - Eptehal Nassar; Mai Rady; Heba Handousa (Future Journal of Pharmaceutical Sciences)
Abstract Background Skin aging is a multifactorial disorder that occurs due to extrinsic and intrinsic factors, where a decrease in natural antioxidant defenses and an imbalance between molecular biomarkers occur. The current study aims to develop nanoliposomes for the dermal delivery of Hs and to investigate their effects on skin biomarkers and skin aging. Methods Chemical profiling performed via high-performance liquid chromatography (HPLC)/ESI‒PDA‒MS revealed enrichment in phenolic metabolite contents. Hs-nanolopeosomes were characterized for their mean size, encapsulation efficiency of Hs and ability to penetrate the skin via confocal microscopy. An aged rat model generated via UV and galactosamine injection was evaluated for reduced glutathione (GSH) and malondialdehyde (MDA) levels, in addition to the levels of collagenase and elastase enzymes in the different study groups, which included a healthy control group, an aged group, a prophylactic group, an aged group treated with Hs-nanoliposomes, and a green tea extract-treated group (positive control). Moreover, the Bcl-2/Bax proteins were determined via ELISA, and MMP-1, MMP-2, MMP-9, and TIMP-1 expression was determined via RT‒qPCR in the study groups. Results Hs-nanoliposomes (~ 400 nm) proved deep skin localization in confocal images. Compared with the aged group and the green tea extract-treated group, the Hs-liposome-treated group presented elevated reduced glutathione and decreased malondialdehyde levels and inhibited collagenase and elastase enzymes. This treatment also decreased the Bcl-2/Bax ratio and downregulated the expression of MMP-1, MMP-2, and MMP-9. However, upregulation of TIMP-1 expression was detected. The outcomes were confirmed by histopathological assays, which revealed reduced saging and collagen damage in the Hs-nanolipid-treated group. Conclusion The present study proposed a potential antiaging nanobased formulation that can deliver Hs extract deep in the dermis layer to prevent the oxidative stress that leads to aging.